Analisis Biaya dan Waktu pada Proyek Pembangunan Gudang dan Musholla Area Mainsub Tuban III-IV dengan Metode Earned Value - Fatimah, Siti; Hepiyanto, Rasio; Dhana, Rio Rahma (Universitas Batanghari Jambi, 2025)
The Warehouse and Musholla Development Project for the Mainsub Tuban II-IV Area is scheduled to be completed within 18 weeks with a contract value of Rp1,543,013,748.08. The purpose of this study was to determine the cost and time performance and the factors that caused the delay and progress of the project. The method used in this study is the Earned Value method which uses elements of cost and time as well as physical performance of the work. Data obtained from the project include the project Time Schedule, Budget Estimate Plan (RAB), weekly project reports, and actual costs, then cost, schedule, variance, performance index analysis was carried out by explaining the problems that emerged during the study. From the results of the analysis, it is known that the costs incurredare lower than the budgeted costs (costs are more efficient than planned) and the completion of the project is according to schedule, which is 18 weeks. However, there was a delay in progress in the 5th and 6th weeks indicated by the SPI (Schedule Performance Index) values of 0.766 and 0.934, which means that the implementation time is slower than the planned schedule caused by technical problems with the implementation of soil excavation that is not in accordance with the plan. The delay in progress can be pursued by accelerating in the 10th week to the 15th week with quite significant progress. The estimated final cost calculation result of the project is Rp1,492,777,469.16 with a completion time of 18 weeks.